Prevalence of non-albicans Candida species isolated from vulvovaginal samples of women and heifers - Nabaa A. Hasan; Zainab A.A. Al-Haddad (International Journal of Medical Toxicology and Legal Medicine, 2024)
The prevalence of non-albicans Candida (NAC) species is increasing globally, leading to pathological changes in both humans and animals. This study aimed to investigate the prevalence of NAC in women and heifers using traditional methods based on phenotypic characterization and antifungal susceptibility. Three hundred vaginal samples were collected-150 from women and 150 from heifers. The samples were cultured on Sabouraud Dextrose Agar (SDA) and HiChromo Agar and identified using the VITEK-2 system. Out of 300 samples,64 sixty four yeast like growth samples were identified via the VITEK-2, 50 tested positive for candidiasis, with 32 positive samples from women and 18 from heifers. Using HiChrome Agar, only one isolate from a heifer and 12 isolates from women were identified as Candida albicans, while the remaining were classified as non-albicans Candida (NAC) species. The VITEK system revealed variability in NAC prevalence between women and heifers. The most prevalent NAC in women was Candida glabrata [13 out of 38 (34.2%)], followed by C. albicans [11 out of 38 (33.8%)] and C. tropicalis [3 out of 38 (7.8%)]. In heifers, the dominant species was C. tropicalis [8 out of 26 (30.7%)], followed by Millerozyma farinosa [6 out of 26, (23.1%)] and C. krusei [5 out of 26 (19.2%)]. The isolation rates of Candida species differed between women and heifers, with C. albicans and C. glabrata being predominant in women, while C. tropicalis and C. krusei were more common in heifers. The study also identified diverse antifungal susceptibility profiles among the Candida species associated with vulvovaginitis. C. glabrata exhibited resistance to fluconazole, micafungin, and caspofungin; C. tropicalis showed varied susceptibility to fluconazole; C. krusei displayed universal resistance to fluconazole and flucytosine; and unexpected fluconazole resistance was observed in C. albicans. This study concluded that NAC is associated with vulvovaginitis in women and was reported here for the first time in heifers.